(untitled) (International Journal of Food and Nutritional Sciences, 2021)
After the independence the then government of Bombay province decided for development of public libraries to implement the recommendations of the Fyzee committee. The Committee also recommended the establishment of one State Central Library at Mumbai and one Regional Library at Pune. The public library is expected to perform various functions. In a democratic society the public library is much more important than other institutions of formal education. The Maharashtra Public Libraries Act envisages development of library service with the help of non-official public libraries. Director is making efforts to develop the services within the framed rules of the Act and the financial resources available.